2021
DOI: 10.1093/g3journal/jkab012
|View full text |Cite|
|
Sign up to set email alerts
|

Application of multi-trait Bayesian decision theory for parental genomic selection

Abstract: In all breeding programs, the decision about which individuals to select and intermate to form the next selection cycle is crucial. The improvement of genetic stocks requires considering multiple traits simultaneously, given that economic value and net genetic merits depend on many traits; therefore, with the advance of computational and statistical tools and genomic selection (GS), researchers are focusing on multi-trait selection. Selection of the best individuals is difficult, especially in traits that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The theory of LFs, used to enhance genetic gain in selection programs, was developed in our previous publications (Villar‐Hernández et al., 2018, 2021). The foundation of LF theory stems from the concept of selection by truncation in single traits and extends to address multitrait selection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theory of LFs, used to enhance genetic gain in selection programs, was developed in our previous publications (Villar‐Hernández et al., 2018, 2021). The foundation of LF theory stems from the concept of selection by truncation in single traits and extends to address multitrait selection.…”
Section: Methodsmentioning
confidence: 99%
“…Following the initial investigation, more recently Villar‐Hernández et al. (2021) conducted multitrait selection using real wheat datasets with four traits and employed the BDT framework and the concept of LFs to explore practical applications and address gaps in a previous study (Villar‐Hernández et al., 2018). The three LFs used for multitrait selection were KL, EnergyS, and MALF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, a model that assumes the closest distribution of SNP effects to their true distribution can achieve the highest reliability in genomic prediction. The GBLUP model assumes that all SNP effects follow the same normal distribution and compresses the effects of all SNPs to the same degree because different models have different assumptions about the distribution of SNP effects (Villar-hernÁndez et al, 2021). Several methods have been proposed to improve the accuracy of genomic prediction in small populations of dairy cattle (Marjanovic et al, 2021), and one effective approach is to use joint reference populations by combining reference data from different populations (Steyn et al, 2019;van Grevenhof et al, 2019).…”
Section: Reliability Of Genetic Evaluation In Joint Reference Populat...mentioning
confidence: 99%
“…Actual breeding often targets multiple traits that are genetically correlated, and the practical routine genetic evaluation of the breeding value is usually calculated using multi‐trait models. Multi‐trait models for GEBV prediction have been reported including Bayesian approaches (Villar‐Hernandez et al, 2021) and the genomic best linear unbiased prediction (GBLUP) method (Karaman et al, 2020). Studies have shown that multi‐trait genomic prediction (MTGP), which accounts for the relationships between the traits, may result in more accurate GEBV than single‐trait genomic prediction (STGP) (Semagn et al, 2022; Song et al, 2020).…”
Section: Introductionmentioning
confidence: 99%